Simulation of Frequency Spectrum of Electric Power Signal - Sayan, H. H.; Kahraman, M.; Koşalay, İ. (Elektronika ir Elektrotechnika, 2010)
In this paper, recursive least squares method (RLSM) which is one of the adaptable classical methods is used. Forgetting factor approach is adapted to RLSM to obtain phase information of voltage signal belonging to an electric power network at first. Then responses of the algorithm are investigated for the signal which has zero magnitude for a specific time interval. And the examination of the frequency spectrum with RLSM method algorithm is done. Simulations are carried out by developing MATLABTM codes. Simulation results of method are presented. Ill. 4, bibl. 9 (in English; abstracts in English, Russian and Lithuanian).